PENEGAKAN HUKUM TERPADU TERHADAP PELAKU UMKM ATAS PELANGGARAN TIDAK MENCANTUMKAN INFORMASI KADALUWARSA PRODUK MAKANAN - Cep Yusup Suparman (JOSH: Journal of Sharia, 2026)
This research is motivated by the fact that many Micro, Small, and Medium Enterprises (MSMEs) in Indonesia still produce and sell food without including expiration date information on product packaging. This condition creates legal problems because it has the potential to harm consumers, endanger public health, and demonstrates weak supervision and law enforcement against business actors. This study aims to analyze the form of integrated law enforcement against MSMEs for violations of not including expiration information on food products and identify inhibiting factors in its implementation. The research method used is qualitative research with an empirical juridical approach. Data were obtained through observation, interviews, documentation, and literature studies, which were then analyzed descriptively qualitatively. The theories used in this study include law enforcement theory, consumer protection theory, and business actor responsibility theory. The results of the study indicate that law enforcement against MSMEs is still not running optimally due to low legal awareness among business actors, lack of socialization regarding the obligation to include expiration information, and limited supervision from relevant agencies. Integrated law enforcement is carried out through guidance, supervision, the imposition of administrative sanctions, and action in accordance with statutory provisions. Therefore, synergy is needed between the government, business actors, and the community to increase legal compliance and provide maximum protection to consumers.